Pathways of adolescent intention for mental health help-seeking: Insights from the theory of planned behavior - Nurlaela Widyarini; Ria Wiyatfi Linsiya (HUMANITAS published by Universitas Ahmad Dahlan., 2025)
Adolescent mental health has emerged as a critical global issue influenced by social changes, technological advancements, and complex life demands. This study, conducted in Jember, East Java, Indonesia, aimed to explore psychosocial factors influencing adolescents' mental health help-seeking intention using the Theory of Planned Behavior (TPB). The research comprised two phases. Phase 1 included 72 students (mean age = 15.86 years, 87% female) from two junior high schools and three senior high schools. These students were interviewed to investigate their beliefs about mental health help-seeking intention through open-ended questions. Phase 2 involved 413 students (mean age = 15.3 years, 52.5% female) from three junior high schools and three senior high schools. This phase developed a model of mental health help-seeking intention based on attitudes, subjective norms, and perceived behavioral control. The study underscored the pivotal role of social support, positive attitudes, and accessible services in shaping adolescents’ intentions to seek mental health assistance. These findings imply that strengthening social support networks, particularly within family and community contexts, promoting positive attitudes and enhancing service accessibility, could substantially increase adolescents' intention to seek help.